EFEKTIFITAS PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH PADA SEKOLAH DASAR 014 TANJUNG REDEB KABUPATEN BERAU: EFEKTIFITAS PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH PADA SEKOLAH DASAR 014 TANJUNG REDEB KABUPATEN BERAU - Arkam (ECO-BUILD, 2025)
The purpose of this study is to find out and analyze the purpose of the research conducted is to determine the effectiveness of the use of school operational assistance funds in State Elementary Schools 014 Tanjung Redeb, Berau Regency. The sample used in this study is data on the Activity Plan and Budget of elementary school 014 Tanjung Redeb, Berau Regency in 2015 – 2022 using quantitative descriptive analysis techniques with an approach using the Effectiveness Ratio indicator. Based on the results of the study, it can be seen that the average level of effectiveness of the use of school operational assistance funds in State Elementary Schools 014 Tanjung Redeb, Berau Regency in 2015-2022 is at an effectiveness ratio of 93.5%, which is on the "Effective" criteria. This means that the hypothesis stating the alleged level of effectiveness of the use of school operational assistance funds in primary schools 014 tanjung redeb berau district is effectively "accepted". Overall, the realization of the 014 primary school budget for each year has the criteria of effectiveness, effectiveness and ineffectiveness. For 2015, 2016, 2017, 2018, 2019, 2021 achieved the effective criteria with an effectiveness ratio of 90% - 100%, For 2020 achieved the criteria quite effectively with an effectiveness ratio of 81.9% and in 2022 achieved the less effective criteria with a ratio of 74.9%.